ANALISIS PERUBAHAN SIFAT MEKANIK DAN STRUKTUR MIKRO BESI COR NODULAR 700 SETELAH MENGALAMI PROSES PERLAKUAN PANAS - Suratman, Rochim; Bandanadjaja, Beny (Mesin, 2002)
Ferro casting ductile 700 (FCD 700) is a ferrous material with carbon content > 2 %. It has pearlitc microstructure with a little amount of ferrite and nodular graphite. In as-cast condition FCD 700 has tensile strength 700 N/mm2 , elongation 2 % min. , hardness 229 â 302 BHN and impact value 7 joule. Heat treatment process is a process that can be executed to ferrous material. With heating the material until a range of austenite temperature then controlling the cooling rate. The objective is to repair or to modify the mechanical properties of material belongs before. In this article thereâs a research about how far the exchange of mechanical properties or microstructure in FCD 700 if it being heat-treated. Cooling rate is given by isothermal and continuous condition. The variation of cooling rate and holding in some isothermal temperature is also accomplished. Research data affirm some gradation of mechanical properties and microstructure. The variety associate with cooling rate and isothermal holding which is performed.